Pneumonectomy: The final cut in a rare incidence of persistent bronchopleural fistula following empyema1. Issue 6 (21st August 2012) - Peters, Robert T.; Child, Frances; Long, Anna‐May; Humphrey, Gillian M.E.; Rakoczy, George
Abstract The incidence of necrotizing pneumonia and empyema complicated by bronchopleural fistula is rising. We describe the case of a 2‐year‐old boy who presented with empyema thoracis and necrotizing pneumonia who developed a bronchopleural fistula. At initial thoracotomy for decortication, necrotic lung was found and resected. He subsequently underwent further thoracotomy, prolonged chest tube drainage and endobronchial glue application attempts to close a bronchopleural fistula. The fistula was only sealed at third thoracotomy and completion pneumonectomy. This case highlights the potential challenges faced when dealing with air leaks in the setting of infection and we discuss the treatment options available. Pediatr Pulmonol. 2013; 48:617–621. © 2012 Wiley Periodicals, Inc.